PENGARUH PERSEPSI KONSUMEN DAN HARGA DALAM KEPUTUSAN PEMBELIAN MAKANAN CEPAT SAJI FRIED CHICKEN PADA PEDAGANG KAKI LIMA DI KOTA SAMBAS - Santo (Lunggi Journal, 2025)
This study aims to analyze the influence of consumer perception and price on purchasing decisions for fried chicken fast food at street vendors in Sambas City. The main focus of this study is to determine the extent to which these two variables influence consumer decisions in purchasing fast food products. The method used in this study is a quantitative approach with a correlational research design. Data were collected through questionnaires distributed to 100 respondents who were students of the Sharia Economics Study Program at IAIS Sambas. The results showed that price had a significant effect on fast food purchasing decisions, with a calculated t value of 4.338 which was greater than the t table of 2.006. On the other hand, consumer perception of product quality did not have a significant effect partially, with a calculated t value of 0.780 which was smaller than the t table. Simultaneously, these two variables had a significant effect on purchasing decisions with an R square value of 0.360, which means that the consumer perception and price variables can explain 36% of the variation in purchasing decisions